PAHAM KEDAULATAN NEGARA DITINJAU DARI SIFAT UNIVERSILATAS HUKUM INTERNASIONAL - Sumartini, Siti (Yustitia, 2019)
The power of theories regarding the principle of sovereignty and equality of the state began to diminish. Every independent country is a sovereign country. they are free to make policies to regulate the economic, political, legal and other systems within their country, however, today's development experiences a shift in meaning, what was previously the authority or full sovereign action of a country has diminished its understanding when the interests of other countries are disrupted or international needs require state sovereignty to be subject to universal rules and highest norms (erga omnes). In this study using a normative juridical approach and descriptive analytical research specifications. The data used in this study are secondary data consisting of primary, secondary and tertiary legal materials. Data obtained through library studies in the form of legislation, books, journals, and authoritative electronic media. The results of this study are 2 (two) explanations, namely First. that state sovereignty does not conflict with the international legal system, that state sovereignty can be used in the framework of forming an international legal system. Secondly, the universality of international law provides restrictions on the sovereignty of the state to be applied properly and the principle of respecting universal values ​​in order to maintain human dignity and their life.